A Photographic Atlas of Nglanggeran Plant Herbarium as a Plant Taxonomy Learning Source - Widodo, Widodo; Luthfi, Muhammad Ja’far; Riyanto, Riyanto (Proceeding International Conference on Religion, Science and Education, 2022)
Mount Nglanggeran is remnants of an ancient volcano located in Baturagung area, Gunung Kidul, Yogyakarta. The landscape and rocky subsoil of Mount Nglanggeran make its plant diversity has been conserved. There is a high diversity of plants that inhabit the area, containing many rare and endemic plants. We developed an interactive photographic atlas of Nglanggeran plant herbarium as a teaching aid. Samples were collected from some parts of Mount Nglanggeran, identified, dried, and processed further to herbaria. The herbaria were photographed. The photographs were processed using software, arranged and formatted into interactive atlas. The result of the research was an interactive atlas of Nglanggeran plant herbarium. The atlas is a useful teaching aid in subject of taxonomy, plant diversity and general biology.